PERBANDINGAN KAPASITAS JALAN ANTARA MODEL PENDEKATAN LALU LINTAS DENGAN MKJI PADA JALAN PERKOTAAN BERLAJUR BANYAK (STUDI KASUS: JALAN RAYA PUPUTAN NITI MANDALA, DENPASAR) - Pranata A., Made Hendi Adi; Negara, I Nyoman Widana; Wikrama, A.A.N.A Jaya (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 18, No. 1, Januari 2014, 2016)
There were three main characteristics affecting traffic flow; those were volume, speed and density. The relationship between those three characteristics was interconnected to each others. This study was intended to investigate the relation between volume-speeddensity on urban road and also to investigate the comparison of road capacity using Greenshield, Greenberg and Underwood Models and MKJI. The location of this study was on Jln. Raya Puputan Niti Mandala which had 3 lanes one-way roads. The Data was analyzed using 3 traffic approaches: Greenshield, Greenberg, Underwood models and MKJI. The largest correlation coefficient (r) was used based on the relation of variable X and Y to gain the maximum volume or capacity (C) which was showed from the best modeling result for the relationship of traffic models. The best model is Greenshield, with (C) values in lanes 1, 2 and 3 are 1340 pcu/hr, 1667 pcu /h, 547 pcu/hr respectively. Based on MKJI model showed that the capacity value for lanes 1 and 2 are 1341 pcu/hr and lane 3 is 1185 pcu/hr. The difference of capacity value on each lane using MKJI was due to the motorist’s behavior who tends to use line 2. This is because in lane 2 contained no side barriers as in lanes 1 and 3.
Keywords: Traffic Model, Greenberg, Greenshield, Underwood, Capacity, Correlation Coefficient, A Multilane Road.